Albert R. Heilig, Ordinances of the City of Tacoma, Washington, at 333-34 (1892) - (:unkn) unknown (My University, 1892)
Prohibited the carrying of a concealed revolver, pistol or other fire arms or any knife (other than an ordinary pocket knife) or any dirk or dagger, slingshot or metal knuckles, or any instrument by the use of which injury could be inflicted upon the person.
Keywords: CARRY - CONCEALED